Fixed Ipad Technology as an Innovation Idea in Chain Accommodation Businesses - ÇALIŞKAN, Gürkan (Journal of Tourism and Gastronomy Studies, 2023)
In this study "Fixed iPad" technology is proposed as an innovative idea in chain accommodation businesses. The use of the proposed technology in accommodation businesses has been discussed and evaluated. In this study, the Diffusion of Innovations Theory is adopted. The idea of a “Fixed iPad” has been proposed to chain accommodation businesses. MAXQDA analysis program was used to visualize the data. The study showed that standards, suitability for the target, cost, and infrastructure are crucial determinants of innovation processes. It has been determined that chain accommodation enterprises cannot make decisions outside the standards. It has been determined that conducting R&D studies can be beneficial in innovation processes. In general, there is the opinion that the proposed innovation can have a positive effect on performance, satisfaction, and competition. A framework for the acceptance of innovations has been developed for chain accommodation businesses. This framework can be a prediction of innovation behavior toward chain accommodation businesses.
Keywords: 9. Industry and infrastructure